(Nie)zwykłe podarunki w (nie)zwykłej codzienności Krasińskich - Łyszkowska, Aldona (W zwierciadle rzeczy, 2022)
The article focuses on the gifts which the closest family of the poet Zygmunt Krasiński used to give to each other. The souvenirs, which were carefully thought out, reflect the feelings, affection, respect, prestige, aristocratic pride, and even the ancestral conservatism. For the purposes of the paper, the voluminous family correspondence, Krasiński’s lyric poetry (poems offered as gifts were the poet’s specialty) and the collections exhibited in the Museum of Romanticism in Opinogóra were analysed. The 19th century gifts exchanged by the Krasińskis are a great source of information about their habits, mentality and relationships between the family members. From behind the souvenirs, there appear sentimental people, gifted with imagination and exquisite taste. Although most of the presents have not survived the vicissitudes of the family, some noteworthy souvenirs have been preserved in the museum collections and in literature.